Insula mediates heartbeat related effects on visual consciousness. (April 2018) - Salomon, Roy; Ronchi, Roberta; Dönz, Jonathan; Bello-Ruiz, Javier; Herbelin, Bruno; Faivre, Nathan; Schaller, Karl; Blanke, Olaf
Abstract: Interoceptive signals, such as the heartbeat, are processed in a network of brain regions including the insular cortex. Recent studies have shown that such signals modulate perceptual and cognitive processing, and that they impact visual awareness. For example, visual stimuli presented synchronously to the heartbeat take longer to enter visual awareness than the same stimuli presented asynchronously to the heartbeat, and this is reflected in anterior insular activation. This finding demonstrated a link between the processing of interoceptive and exteroceptive signals as well as visual awareness in the insular cortex. The advantage for visual stimuli which are asynchronous to the heartbeat to enter visual consciousness may indicate a role for the anterior insula in the suppression of the sensory consequences of cardiac signals. Here, we present data from the detailed investigation of two patients with insular lesions (as well as four patients with non-insular lesions and healthy age matched controls) indicating that a lesion of the anterior insular cortex, but not of other regions, abolished this cardio-visual suppression effect. The present data provide causal evidence for the role of the anterior insula in the integration of internal interoceptive and external sensory signals for visual awareness.